Local and Urban Development in the European Union - Cristina Brasili (European Regional Science Association (ERSA), 2011)
Starting from the definition of local development as a process of cooperation and change managed by local actors whose main goal is producing collective goods for the local community I would like to consider the factors which favour the possibility of making the process start. In the first part it will be presented the several programs for a sustainable urban development by the European Commission (Urban I, Urban II, Leipzig Charter) from Nineties up to now. Moreover, passing through the concept of territorial capital it will be design the linkages between local and urban development in the EU in order to arrange effective policies to improve the local and urban development. Therefore, politics of local development must intervene to increase cities territorial capital; this could seem to be obvious but it is less evident than quantifying territorial capital, in particular the cities one. The second part of the paper has just been finalized to find out seven essential components of territorial capital: productive, cognitive, social, relational, environmental, settlement, infrastructural components. Selecting one or more variables for each one of these components (with the exception of the relational one which we can't quantify) they can represent the territorial capital for European cities. The used variables are taken from Eurostat Urban Audit database about European cities, they refer to 2006/2007 biennium and they regard 118 cities of Belgium, Denmark, Germany, Spain, France, Esthonia, Italy, Latvia, Lithuania, Hungary, Holland, Slovakia, Slovenia, Finland and United Kingdom. Synthesizing the information given by the chosen variables (through the statistical analysis of the Principal Components) it will be specify six groups of cities which are as homogeneous as possible for presence of territorial capital, this is very useful to better addressed the policies to the local and, more specifically, urban development.
Keywords: 330